PELATIHAN PEMBUATAN LKPD IPA MULTIMEDIA DENGAN PROGRAM PHET PADA GURU SD UNTUK MEMFASILITASI TAHAP BERPIKIR KONKRET SISWA SD DI TULUNGAGUNG - Permatasari, Faudina (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
The use of PhET simulations is an alternative in delivering science concepts in science learning activities in elementary school. However, not all teachers can operate and design learning activities using PhET simulations. The target of this training is the first elementary school teachers in Tulungagaung City. Training activities were carried out through zoom so that teachers from various sub-districts in Tulungagaung could participate. The method used was training and workshops on the application of technology in learning activities. The final result of the training activities is that each teacher can apply PhET simulations media in designing learning activities in the classroom.